RESPON EVAPOTRANSPIRASI TANAMAN PADI (Oryza Sativa L.) VARIETAS PERMATA DAN SERAYU TERHADAP VARIASI KETEBALAN TANAH MENGGUNAKAN METODE SYSTEM OF RICE INTENSIFICATION (SRI) DI DESA RASI, KABUPATEN MINAHASA TENGGARA - Greydi F. H. Punusingon; Daniel P. M. Ludong; Johannes E. X. Rogi (Universitas Sam Ratulangi, 2021)
The purpose of this study was to calculate the amount of water required during the growth phases of the rice var. Permata and Serayu with soil layer thickness of 25 cm and 35 cm.This research was conducted in September - December 2019 in Rasi Village, Ratahan District, Southeast Minahasa Regency. The research was carried out experimentally and the observed data in the field were analyzed descriptively. This study consisted of two treatment factors, i.e. variety (Serayu and Permata) and the thickness of the cultivated soil (25 and 35 cm). The rice plants were planted in and in theiron boxes (60 X 60 cm) in the paddy fields. The total Evapotranspiration or water requirement for rice planted the iron boxeswere188 and 254 L, respectively, for soil depth of 25 and 35 cm in Serayu. For the Permata variety with a soil depth of 25 and 35 cm, the water requirement were175 and 231L, respectively.